Selling Destinations : Geography for the travel professional - Mancini, Marc, ....- (California : Marc Mancini Seminars and consulting Inc, 2008)
The fifth Canadian edition of Selling Destinations: Geography for the travel professional is an entertaining, practical, and highly readable combination workbook/textbook that approaches geography from a travel industry perspective.
Keywords: Tourisme; travel